Wave-absorbing stealth composite material for unmanned aerial vehicle and preparation method thereof

The composite material of modified carbon nanotubes and iron oxide-coated polythiophene addresses the limitations of existing UAV absorbent materials by providing enhanced electromagnetic wave absorption and stealth capabilities through combined electrical and magnetic loss mechanisms.

CN120310199APending Publication Date: 2025-07-15QINGDAO JINGXIN SEMICON CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510450356.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-11
Publication Date
2025-07-15

AI Technical Summary

Technical Problem

The existing wave-absorbing stealth materials have problems with low wave absorption efficiency and narrow wave absorption frequency band on drones, which is difficult to meet the high stealth effect in multi-band electromagnetic environments.

Method used

A composite material with modified polythiophene coated with the external coating of the loaded carbon nanotubes is used to achieve efficient absorption of electromagnetic waves through the synergy between the loaded carbon nanotubes and the modified thiophene.

Benefits of technology

It significantly improves the stealth effect of the drone, can effectively absorb and dissipate external electromagnetic waves, reduces the probability of being detected by radar, and widens the wave absorption frequency band.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005353825000000131
    Figure BDA0005353825000000131
Patent Text Reader

Abstract

The invention relates to the field of wave-absorbing stealth materials, in particular to a wave-absorbing stealth composite material for an unmanned aerial vehicle and a preparation method of the wave-absorbing stealth composite material, and is used for solving the problems that an existing wave-absorbing stealth material has the defects of low wave-absorbing efficiency and narrow wave-absorbing frequency band, and the requirement of the unmanned aerial vehicle for a high stealth effect in a multi-frequency-band electromagnetic environment is difficult to meet. According to the preparation method, ferroferric oxide is loaded on carboxylated carbon nanotubes, the outer surfaces of the carboxylated carbon nanotubes are coated with fluorine-containing polythiophene, the carboxylated carbon nanotubes in the composite material absorb electromagnetic wave energy through conductive loss, and the ferroferric oxide in the composite material converts electromagnetic energy into heat energy through hysteresis loss and eddy-current loss. The fluorine-containing polythiophene in the composite material is used as a conductive polymer, so that the conductive loss is further enhanced, under the synergistic effect of the fluorine-containing polythiophene, the conductive polymer and the conductive polymer, the efficient absorption of electromagnetic waves is realized, the absorption and shielding of the electromagnetic waves can be effectively realized, and the stealth effect of the unmanned aerial vehicle is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of microwave absorbing stealth materials, and particularly to a microwave absorbing stealth composite material for unmanned aerial vehicles and a preparation method thereof. Background Art

[0002] With the rapid development of unmanned aerial vehicle (UAV) technology, its applications in military reconnaissance, civilian aerial photography, logistics transportation and other fields are becoming increasingly widespread. Especially in military reconnaissance, military surveillance and military strike missions, UAVs have been widely used due to their advantages such as flexibility, stealth and cost-effectiveness. However, with the rapid development of radar detection technology, UAVs face a great risk of being detected and attacked. To improve the survival ability and combat effectiveness of UAVs, stealth technology has become the key.

[0003] The traditional solution is to spray a coating containing microwave absorbing stealth material on the UAV body to form a stealth coating. Therefore, microwave absorbing stealth material is the core to achieve UAV stealth. At present, the existing microwave absorbing stealth materials have the disadvantages of low microwave absorption efficiency and narrow microwave absorption bandwidth, and it is difficult to meet the requirements of high stealth effect of UAVs in multi-band electromagnetic environment. Therefore, it is of great significance to develop a microwave absorbing stealth composite material for UAVs and a preparation method thereof. Summary of the Invention

[0004] In order to overcome the above technical problems, the purpose of the present invention is to provide a microwave absorbing stealth composite material for UAVs and a preparation method thereof, which solves the problems that the existing microwave absorbing stealth materials have the disadvantages of low microwave absorption efficiency and narrow microwave absorption bandwidth, and it is difficult to meet the requirements of high stealth effect of UAVs in multi-band electromagnetic environment.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] A microwave absorbing stealth composite material for UAVs is formed by externally coating modified polythiophene on load-type carbon nanotubes. Among them, the load-type carbon nanotubes are formed by carboxylated carbon nanotubes loading iron oxide. Among them, the modified polythiophene is polymerized from modified thiophene monomers.

[0007] As a further scheme of the present invention: the load-type carbon nanotubes are prepared by the following steps:

[0008] Add carboxylated carbon nanotubes, ferric chloride hexahydrate, ferrous sulfate heptahydrate, and deionized water into a three-necked flask equipped with a stirrer, a thermometer, a gas pipe, and a constant pressure dropping funnel. Introduce nitrogen for protection. Stir and react for 10 - 20 min under the conditions of a temperature of 25 - 30 °C and a stirring rate of 200 - 300 r / min. Then raise the temperature to 50 - 55 °C and continue to stir and react for 30 - 35 min. After that, gradually add aqueous ammonia solution dropwise while stirring, control the dropping rate at 1 - 2 drops / s. After the dropping is completed, continue to stir and react for 5 - 10 min. Then add absolute ethanol and continue to stir and react for 3 - 4 h. After the reaction is completed, cool the reaction product to room temperature. Then perform solid-liquid separation by the method of magnetic attraction. Wash the solid with distilled water 3 - 5 times. Then place it in a vacuum drying oven and dry it at a temperature of 60 - 65 °C for 3 - 4 h to obtain the supported carbon nanotubes.

[0009] As a further scheme of the present invention: The dosage ratio of the carboxylated carbon nanotubes, ferric chloride hexahydrate, ferrous sulfate heptahydrate, deionized water, aqueous ammonia solution, and absolute ethanol is 2 g : 3 mmol : 6 mmol : 40 - 50 mL : 20 - 25 mL : 10 - 15 mL.

[0010] As a further scheme of the present invention: The mass fraction of the aqueous ammonia solution is 26 - 28%.

[0011] As a further scheme of the present invention: The carboxylated carbon nanotubes are prepared by the following steps:

[0012] Add carbon nanotubes, concentrated sulfuric acid, and concentrated nitric acid into a three-necked flask equipped with a stirrer and a thermometer. Stir and react for 10 - 20 min under the conditions of a temperature of 25 - 30 °C and a stirring rate of 200 - 300 r / min. Then raise the temperature to 80 - 85 °C and continue to stir and react for 6 - 8 h. After the reaction is completed, cool the reaction product to room temperature. Then centrifuge. Wash the precipitate with sodium bicarbonate solution and deionized water 3 - 5 times. Then place it in a vacuum drying oven and dry it at a temperature of 60 - 65 °C for 3 - 4 h to obtain the carboxylated carbon nanotubes.

[0013] As a further scheme of the present invention: The dosage ratio of the carbon nanotubes, concentrated sulfuric acid, and concentrated nitric acid is 2 g : 10 - 15 mL : 30 - 35 mL.

[0014] As a further scheme of the present invention: The diameter of the carbon nanotubes is 30 - 40 nm and the length is 5 - 10 μm.

[0015] As a further scheme of the present invention: The mass fraction of the concentrated sulfuric acid is 96 - 98%.

[0016] As a further solution of the present invention: the concentrated nitric acid has a mass fraction of 66-68%.

[0017] As a further solution of the present invention: the mass fraction of the sodium bicarbonate solution is 5-10%.

[0018] As a further solution of the present invention: the modified thiophene monomer is prepared by the following steps:

[0019] Thiophene-3-acetic acid, hexafluoroisopropanol, 4-dimethylaminopyridine, N,N'-carbonyldiimidazole and chloroform are added to a three-necked flask equipped with a stirrer and a thermometer, and stirred at a temperature of 25-30 °C and a stirring rate of 200-300 r / min for 10-20 min. Then, the temperature is raised to 80-85 °C and stirring is continued for 10-12 h. After the reaction is completed, the reaction product is cooled to room temperature, and then the solvent is removed by rotary evaporation. Then it is added to distilled water, and then extracted with dichloromethane 2-3 times. The extraction liquids are combined and dried with anhydrous magnesium sulfate, and then vacuum filtered. The filtrate is rotary evaporated to remove the solvent, and then purified by column chromatography with a mixed eluent to obtain the modified thiophene monomer.

[0020] As a further solution of the present invention: the dosage ratio of the thiophene-3-acetic acid, hexafluoroisopropanol, 4-dimethylaminopyridine, N,N'-carbonyldiimidazole and chloroform is 20 mmol: 23-25 mmol: 1.1-1.5 g: 1.3-1.7 g: 40-50 mL.

[0021] As a further solution of the present invention: the mixed eluent is a mixture of ethyl acetate and n-hexane in a volume ratio of 1:8-10.

[0022] As a further solution of the present invention: a preparation method of a wave-absorbing stealth composite material for an unmanned aerial vehicle includes the following steps:

[0023] The supported carbon nanotubes and chloroform are added to a three-necked flask equipped with a stirrer and a thermometer, and ultrasonically dispersed for 2-3 h under the condition of an ultrasonic frequency of 30-40 kHz. Then, the modified thiophene monomer is added and stirred at a temperature of 25-30 °C and a stirring rate of 200-300 r / min for 2-3 h. Then, anhydrous ferric chloride is added and stirring is continued for 20-30 h. After the reaction is completed, the reaction product is vacuum filtered, and the filter cake is washed 3-5 times with anhydrous ethanol and distilled water in sequence, and then placed in a vacuum drying oven and dried at a temperature of 50-55 °C for 8-10 h to obtain the wave-absorbing stealth composite material for an unmanned aerial vehicle.

[0024] As a further solution of the present invention: the dosage ratio of the supported carbon nanotubes, chloroform, modified thiophene monomer and anhydrous ferric chloride is 1 g: 50 - 60 mL: 10 - 30 mmol: 40 - 80 mmol.

[0025] Advantages of the present invention:

[0026] An electromagnetic wave absorbing and stealth composite material for unmanned aerial vehicles and a preparation method thereof according to the present invention. The electromagnetic wave absorbing and stealth composite material is composed of modified polythiophene coated on the outside of supported carbon nanotubes. The supported carbon nanotubes are composed of carboxylated carbon nanotubes loaded with iron tetroxide, and the modified polythiophene is polymerized from modified thiophene monomers. In the preparation method, carboxylated carbon nanotubes are loaded with iron tetroxide, and fluorinated polythiophene is coated on the outer surface. The carboxylated carbon nanotubes in the composite material absorb electromagnetic wave energy through conductive loss. The iron tetroxide in the composite material converts electromagnetic energy into heat energy through hysteresis loss and eddy current loss. The fluorinated polythiophene in the composite material, as a conductive polymer, further enhances the conductive loss. Under the synergistic effect of the three, efficient absorption of electromagnetic waves is achieved, and effective absorption and shielding of electromagnetic waves are realized. By using this composite material, the unmanned aerial vehicle can effectively absorb and dissipate external electromagnetic waves during operation, thereby greatly reducing the probability of being detected by radar and significantly improving the stealth effect of the unmanned aerial vehicle.

[0027] During the preparation of the electromagnetic wave absorbing and stealth composite material for unmanned aerial vehicles, a supported carbon nanotube was first prepared. First, acid treatment was carried out using carbon nanotubes as raw materials, which can effectively remove impurities on the surface of carbon nanotubes and introduce a large number of carboxyl groups at the same time to obtain carboxylated carbon nanotubes. Then, the carboxylated carbon nanotubes were loaded. The carboxyl groups can effectively interact with iron tetroxide nanoparticles to form a stable complex, and supported carbon nanotubes were obtained. The electrons in the carbon nanotubes of the supported carbon nanotubes can move quickly, generating significant conductance loss. At the same time, polar groups such as carboxyl groups will undergo orientation polarization, further generating polarization loss, converting electromagnetic energy into heat energy and consuming it. Iron tetroxide is a magnetic material with a high magnetic permeability. The hysteresis loss and eddy current loss are generated by iron tetroxide. Under the synergistic effect of the two, the magnetic loss characteristics of iron tetroxide and the electrical loss characteristics of carbon nanotubes complement each other, enabling the composite material to effectively absorb electromagnetic waves in different frequency bands.

[0028] In the process of preparing the microwave-absorbing stealth composite material for unmanned aerial vehicles (UAVs), a modified thiophene monomer was first prepared. Thiophene-3-acetic acid and hexafluoroisopropanol were reacted, and the carboxyl group on thiophene-3-acetic acid and the hydroxyl group on hexafluoroisopropanol underwent an esterification reaction, thereby introducing a large number of fluorine atoms to obtain the modified thiophene monomer. Finally, the modified thiophene monomer was polymerized under the catalysis of anhydrous ferric chloride to form polythiophene containing a large number of fluorine atoms, and the polythiophene was used to wrap the supported carbon nanotubes. After wrapping, the dispersibility of the supported carbon nanotubes can be improved, and the aggregation of the supported carbon nanotubes can be avoided, so that when it is applied to UAVs, a uniform effect can be achieved. In addition, polythiophene itself has a unique conjugated structure and electrical properties, and its conjugated system can interact with electromagnetic waves to generate polarization and conductance loss. At the same time, the introduction of fluorine atoms increases the electron cloud density and polarizability of the material, enhances the absorption ability of electromagnetic waves, further improves the electromagnetic wave absorption effect of the composite material, optimizes the microwave-absorbing performance, and further broadens the microwave-absorbing frequency band. In addition, the introduction of fluorine atoms can also form a dense protective film, which can prevent external moisture, oxygen, sunlight, chemical substances, etc. from contacting the internal carbon nanotubes and iron tetroxide, thereby maintaining the stability of the structure and performance of the composite material, enabling the composite material to maintain stable performance under complex environmental conditions, and extending the service life of UAVs. Detailed implementation manners

[0029] The following will combine the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.

[0030] Example 1:

[0031] This example is a microwave-absorbing stealth composite material for UAVs, which is composed of modified polythiophene coated on the outside of supported carbon nanotubes. Among them, the supported carbon nanotubes are composed of carboxylated carbon nanotubes loaded with iron tetroxide, and the modified polythiophene is polymerized from modified thiophene monomers.

[0032] Example 2:

[0033] This example is a preparation method of a microwave-absorbing stealth composite material for UAVs, including the following steps:

[0034] Step 1: Add 2 g of carbon nanotubes, 10 mL of concentrated sulfuric acid with a mass fraction of 96%, and 30 mL of concentrated nitric acid with a mass fraction of 66% into a three-necked flask equipped with a stirrer and a thermometer. Stir and react for 10 min under the conditions of a temperature of 25°C and a stirring rate of 200 r / min. Then, continue to stir and react for 6 h under the condition of heating to 80°C. After the reaction is completed, cool the reaction product to room temperature, and then centrifuge. Wash the precipitate successively with a sodium bicarbonate solution with a mass fraction of 5% and deionized water three times. Then, place it in a vacuum drying oven and dry it for 3 h under the condition of a temperature of 60°C to obtain carboxylated carbon nanotubes;

[0035] Step 2: Add 2 g of carboxylated carbon nanotubes, 3 mmol of ferric chloride hexahydrate, 6 mmol of ferrous sulfate heptahydrate, and 40 mL of deionized water into a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube, and a constant pressure dropping funnel. Introduce nitrogen for protection. Stir and react for 10 min under the conditions of a temperature of 25°C and a stirring rate of 200 r / min. Then, continue to stir and react for 30 min under the condition of heating to 50°C. Then, dropwise add 20 mL of an ammonia water solution with a mass fraction of 26% drop by drop while stirring, control the dropping rate at 1 drop / s. After the dropping is completed, continue to stir and react for 5 min. Then, add 10 mL of absolute ethanol and continue to stir and react for 3 h. After the reaction is completed, cool the reaction product to room temperature, and then perform solid-liquid separation by magnetic attraction method. Wash the solid three times with distilled water. Then, place it in a vacuum drying oven and dry it for 3 h under the condition of a temperature of 60°C to obtain supported carbon nanotubes;

[0036] Step 3: Add 20 mmol of thiophene-3-acetic acid, 23 mmol of hexafluoroisopropanol, 1.1 g of 4-dimethylaminopyridine, 1.3 g of N,N'-carbonyldiimidazole, and 40 mL of chloroform into a three-necked flask equipped with a stirrer and a thermometer. Stir and react for 10 min under the conditions of a temperature of 25°C and a stirring rate of 200 r / min. Then, continue to stir and react for 10 h under the condition of heating to 80°C. After the reaction is completed, cool the reaction product to room temperature, and then rotate the evaporator to remove the solvent. Then, add it to distilled water, and then extract it twice with dichloromethane. Combine the extraction liquids and dry them with anhydrous magnesium sulfate. Then, perform vacuum filtration. Rotate the evaporator to remove the solvent from the filtrate, and then perform column chromatography purification with a mixed eluent composed of ethyl acetate and n-hexane in a volume ratio of 1:8 to obtain modified thiophene monomers;

[0037] Step 4: Add 1 g of supported carbon nanotubes and 50 mL of chloroform into a three-necked flask equipped with a stirrer and a thermometer, ultrasonically disperse for 2 h under the condition of an ultrasonic frequency of 30 kHz, then add 10 mmol of modified thiophene monomer and stir and react for 2 h at a temperature of 25 °C and a stirring rate of 200 r / min. Then add 40 mmol of anhydrous ferric chloride and continue to stir and react for 20 h. After the reaction is completed, vacuum filter the reaction product, wash the filter cake with absolute ethanol and distilled water three times in sequence, and then place it in a vacuum drying oven and dry for 8 h at a temperature of 50 °C to obtain the wave-absorbing stealth composite material for unmanned aerial vehicles.

[0038] Example 3:

[0039] This example is a preparation method of a wave-absorbing stealth composite material for unmanned aerial vehicles, which includes the following steps:

[0040] Step 1: Add 2 g of carbon nanotubes, 12 mL of concentrated sulfuric acid with a mass fraction of 97% and 32 mL of concentrated nitric acid with a mass fraction of 67% into a three-necked flask equipped with a stirrer and a thermometer, stir and react for 15 min at a temperature of 28 °C and a stirring rate of 250 r / min, then continue to stir and react for 7 h under the condition of heating to 82 °C. After the reaction is completed, cool the reaction product to room temperature, then centrifuge, wash the precipitate with a sodium bicarbonate solution with a mass fraction of 8% and deionized water four times in sequence, and then place it in a vacuum drying oven and dry for 3.5 h at a temperature of 62 °C to obtain carboxylated carbon nanotubes;

[0041] Step 2: Add 2 g of carboxylated carbon nanotubes, 3 mmol of ferric chloride hexahydrate, 6 mmol of ferrous sulfate heptahydrate and 45 mL of deionized water into a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube and a constant pressure dropping funnel, introduce nitrogen for protection, stir and react for 15 min at a temperature of 28 °C and a stirring rate of 250 r / min, then continue to stir and react for 32 min under the condition of heating to 52 °C. Then, while stirring, gradually add 22 mL of ammonia water with a mass fraction of 27% dropwise, control the dropping rate at 1 drop / s. After the dropping is completed, continue to stir and react for 8 min, then add 12 mL of absolute ethanol and continue to stir and react for 3.5 h. After the reaction is completed, cool the reaction product to room temperature, then carry out solid-liquid separation by the method of magnetic attraction, wash the solid with distilled water four times, and then place it in a vacuum drying oven and dry for 3.5 h at a temperature of 62 °C to obtain supported carbon nanotubes;

[0042] Step 3: Add 20 mmol of thiophene-3-acetic acid, 24 mmol of hexafluoroisopropanol, 1.3 g of 4-dimethylaminopyridine, 1.5 g of N,N'-carbonyldiimidazole, and 45 mL of chloroform into a three-necked flask equipped with a stirrer and a thermometer. Stir and react for 15 min under the conditions of a temperature of 28 °C and a stirring rate of 250 r / min. Then, continue to stir and react for 11 h under the condition of heating to 82 °C. After the reaction is completed, cool the reaction product to room temperature, then rotary evaporate to remove the solvent. Then add it to distilled water, and extract it twice with dichloromethane. Combine the extraction solutions and dry them with anhydrous magnesium sulfate. Then perform vacuum filtration. Rotary evaporate the filtrate to remove the solvent, and then purify it by column chromatography with a mixed eluent composed of ethyl acetate and n-hexane in a volume ratio of 1:9 to obtain the modified thiophene monomer;

[0043] Step 4: Add 1 g of supported carbon nanotubes and 55 mL of chloroform into a three-necked flask equipped with a stirrer and a thermometer. Ultrasonically disperse for 2.5 h under the condition of an ultrasonic frequency of 35 kHz. Then add 20 mmol of the modified thiophene monomer and stir and react for 2.5 h under the conditions of a temperature of 28 °C and a stirring rate of 250 r / min. Then add 60 mmol of anhydrous ferric chloride and continue to stir and react for 25 h. After the reaction is completed, perform vacuum filtration on the reaction product. Wash the filter cake 4 times with anhydrous ethanol and distilled water in sequence. Then place it in a vacuum drying oven and dry it for 9 h under the condition of a temperature of 52 °C to obtain the radar-absorbing stealth composite material for unmanned aerial vehicles.

[0044] Example 4:

[0045] This example is a preparation method of a radar-absorbing stealth composite material for unmanned aerial vehicles, including the following steps:

[0046] Step 1: Add 2 g of carbon nanotubes, 15 mL of concentrated sulfuric acid with a mass fraction of 98%, and 35 mL of concentrated nitric acid with a mass fraction of 68% into a three-necked flask equipped with a stirrer and a thermometer. Stir and react for 20 min under the conditions of a temperature of 30 °C and a stirring rate of 300 r / min. Then, continue to stir and react for 8 h under the condition of heating to 85 °C. After the reaction is completed, cool the reaction product to room temperature, then centrifuge. Wash the precipitate 5 times with a 10% sodium bicarbonate solution and deionized water in sequence. Then place it in a vacuum drying oven and dry it for 4 h under the condition of a temperature of 65 °C to obtain carboxylated carbon nanotubes;

[0047] Step 2: Add 2 g of carboxylated carbon nanotubes, 3 mmol of ferric chloride hexahydrate, 6 mmol of ferrous sulfate heptahydrate, and 50 mL of deionized water into a three-necked flask equipped with a stirrer, a thermometer, a gas pipe, and a constant-pressure dropping funnel. Introduce nitrogen for protection. Stir and react for 20 min under the conditions of a temperature of 30 °C and a stirring rate of 300 r / min. Then, raise the temperature to 55 °C and continue to stir and react for 35 min. After that, gradually add 25 mL of 28% ammonia water drop by drop while stirring, control the dropping rate at 2 drops / s. After the dropping is completed, continue to stir and react for 10 min. Then, add 15 mL of absolute ethanol and continue to stir and react for 4 h. After the reaction is completed, cool the reaction product to room temperature. Then, perform solid-liquid separation by magnetic attraction method. Wash the solid with distilled water 5 times. Then, place it in a vacuum drying oven and dry it for 4 h at a temperature of 65 °C to obtain the supported carbon nanotubes;

[0048] Step 3: Add 20 mmol of thiophene-3-acetic acid, 25 mmol of hexafluoroisopropanol, 1.5 g of 4-dimethylaminopyridine, 1.7 g of N,N'-carbonyldiimidazole, and 50 mL of chloroform into a three-necked flask equipped with a stirrer and a thermometer. Stir and react for 20 min under the conditions of a temperature of 30 °C and a stirring rate of 300 r / min. Then, raise the temperature to 85 °C and continue to stir and react for 12 h. After the reaction is completed, cool the reaction product to room temperature. Then, remove the solvent by rotary evaporation. Then, add it to distilled water. Then, extract it with dichloromethane 3 times. Combine the extraction liquids and dry them with anhydrous magnesium sulfate. Then, perform vacuum filtration. Rotate and evaporate the filtrate to remove the solvent. Then, perform column chromatography purification with a mixed eluent composed of ethyl acetate and n-hexane in a volume ratio of 1:10 to obtain the modified thiophene monomer;

[0049] Step 4: Add 1 g of supported carbon nanotubes and 60 mL of chloroform into a three-necked flask equipped with a stirrer and a thermometer. Ultrasonically disperse for 3 h under the condition of an ultrasonic frequency of 40 kHz. Then, add 30 mmol of the modified thiophene monomer and stir and react for 3 h under the conditions of a temperature of 30 °C and a stirring rate of 300 r / min. Then, add 80 mmol of anhydrous ferric chloride and continue to stir and react for 30 h. After the reaction is completed, perform vacuum filtration on the reaction product. Wash the filter cake with absolute ethanol and distilled water 5 times respectively. Then, place it in a vacuum drying oven and dry it for 10 h at a temperature of 55 °C to obtain the radar-absorbing stealth composite material for unmanned aerial vehicles.

[0050] Comparative Example 1:

[0051] This comparative example is a preparation method of a radar-absorbing stealth composite material for unmanned aerial vehicles, including the following steps:

[0052] Step 1: Add 2 g of carbon nanotubes, 15 mL of concentrated sulfuric acid with a mass fraction of 98%, and 35 mL of concentrated nitric acid with a mass fraction of 68% into a three-necked flask equipped with a stirrer and a thermometer. Stir and react for 20 min under the conditions of a temperature of 30 °C and a stirring rate of 300 r / min. Then, continue to stir and react for 8 h under the condition of raising the temperature to 85 °C. After the reaction is completed, cool the reaction product to room temperature, then centrifuge. Wash the precipitate successively with a 10% sodium bicarbonate solution and deionized water 5 times. Then, place it in a vacuum drying oven and dry it for 4 h under the condition of a temperature of 65 °C to obtain carboxylated carbon nanotubes;

[0053] Step 2: Add 2 g of carboxylated carbon nanotubes, 3 mmol of ferric chloride hexahydrate, 6 mmol of ferrous sulfate heptahydrate, and 50 mL of deionized water into a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube, and a constant pressure dropping funnel. Introduce nitrogen for protection. Stir and react for 20 min under the conditions of a temperature of 30 °C and a stirring rate of 300 r / min. Then, continue to stir and react for 35 min under the condition of raising the temperature to 55 °C. Then, gradually add 25 mL of a 28% ammonia water solution drop by drop while stirring, control the dropping rate at 2 drops / s. After the dropping is completed, continue to stir and react for 10 min. Then, add 15 mL of absolute ethanol and continue to stir and react for 4 h. After the reaction is completed, cool the reaction product to room temperature, then perform solid-liquid separation by the method of magnetic attraction. Wash the solid 5 times with distilled water. Then, place it in a vacuum drying oven and dry it for 4 h under the condition of a temperature of 65 °C to obtain the wave-absorbing stealth composite material for drones.

[0054] Comparative Example 2:

[0055] This comparative example is a preparation method of a wave-absorbing stealth composite material for drones, including the following steps:

[0056] Step 1: Add 2 g of carbon nanotubes, 15 mL of concentrated sulfuric acid with a mass fraction of 98%, and 35 mL of concentrated nitric acid with a mass fraction of 68% into a three-necked flask equipped with a stirrer and a thermometer. Stir and react for 20 min under the conditions of a temperature of 30 °C and a stirring rate of 300 r / min. Then, continue to stir and react for 8 h under the condition of raising the temperature to 85 °C. After the reaction is completed, cool the reaction product to room temperature, then centrifuge. Wash the precipitate successively with a 10% sodium bicarbonate solution and deionized water 5 times. Then, place it in a vacuum drying oven and dry it for 4 h under the condition of a temperature of 65 °C to obtain carboxylated carbon nanotubes;

[0057] Step 2: Add 2 g of carboxylated carbon nanotubes, 3 mmol of ferric chloride hexahydrate, 6 mmol of ferrous sulfate heptahydrate, and 50 mL of deionized water into a three-necked flask equipped with a stirrer, a thermometer, a gas pipe, and a constant-pressure dropping funnel. Introduce nitrogen for protection. Stir and react for 20 min under the conditions of a temperature of 30 °C and a stirring rate of 300 r / min. Then, continue to stir and react for 35 min under the condition of heating to 55 °C. After that, slowly add 25 mL of 28% ammonia water drop by drop while stirring, control the dropping rate at 2 drops / s. After the dropping is completed, continue to stir and react for 10 min. Then, add 15 mL of absolute ethanol and continue to stir and react for 4 h. After the reaction is completed, cool the reaction product to room temperature, and then perform solid-liquid separation by the method of magnetic attraction. Wash the solid 5 times with distilled water, and then place it in a vacuum drying oven and dry it for 4 h at a temperature of 65 °C to obtain the supported carbon nanotubes;

[0058] Step 3: Add 1 g of supported carbon nanotubes and 60 mL of chloroform into a three-necked flask equipped with a stirrer and a thermometer. Ultrasonically disperse for 3 h under the condition of an ultrasonic frequency of 40 kHz. Then, add 30 mmol of thiophene and stir and react for 3 h under the conditions of a temperature of 30 °C and a stirring rate of 300 r / min. After that, add 80 mmol of anhydrous ferric chloride and continue to stir and react for 30 h. After the reaction is completed, vacuum filter the reaction product. Wash the filter cake 5 times with absolute ethanol and distilled water in sequence, and then place it in a vacuum drying oven and dry it for 10 h at a temperature of 55 °C to obtain the microwave absorption stealth composite material for unmanned aerial vehicles.

[0059] Comparative Example 3:

[0060] This comparative example is a preparation method of a microwave absorption stealth composite material for unmanned aerial vehicles, including the following steps:

[0061] Step 1: Add 2 g of carbon nanotubes, 15 mL of 98% concentrated sulfuric acid, and 35 mL of 68% concentrated nitric acid into a three-necked flask equipped with a stirrer and a thermometer. Stir and react for 20 min under the conditions of a temperature of 30 °C and a stirring rate of 300 r / min. Then, continue to stir and react for 8 h under the condition of heating to 85 °C. After the reaction is completed, cool the reaction product to room temperature, and then centrifuge. Wash the precipitate 5 times with 10% sodium bicarbonate solution and deionized water in sequence, and then place it in a vacuum drying oven and dry it for 4 h at a temperature of 65 °C to obtain carboxylated carbon nanotubes;

[0062] Step 2: Add 1 g of carboxylated carbon nanotubes and 60 mL of chloroform into a three-necked flask equipped with a stirrer and a thermometer, ultrasonically disperse for 3 h under the condition of an ultrasonic frequency of 40 kHz, then add 30 mmol of thiophene and stir and react for 3 h at a temperature of 30 °C and a stirring rate of 300 r / min. Then add 80 mmol of anhydrous ferric chloride and continue to stir and react for 30 h. After the reaction is completed, vacuum filter the reaction product, wash the filter cake with absolute ethanol and distilled water 5 times in sequence, and then place it in a vacuum drying oven and dry for 10 h at a temperature of 55 °C to obtain the radar-absorbing stealth composite material for unmanned aerial vehicles.

[0063] Comparative Example 4:

[0064] This comparative example is a preparation method of a radar-absorbing stealth composite material for unmanned aerial vehicles, including the following steps:

[0065] Step 1: Add 2 g of carbon nanotubes, 15 mL of concentrated sulfuric acid with a mass fraction of 98% and 35 mL of concentrated nitric acid with a mass fraction of 68% into a three-necked flask equipped with a stirrer and a thermometer, stir and react for 20 min at a temperature of 30 °C and a stirring rate of 300 r / min, then continue to stir and react for 8 h under the condition of heating to 85 °C. After the reaction is completed, cool the reaction product to room temperature, then centrifuge, wash the precipitate with a 10% sodium bicarbonate solution and deionized water 5 times in sequence, and then place it in a vacuum drying oven and dry for 4 h at a temperature of 65 °C to obtain carboxylated carbon nanotubes;

[0066] Step 2: Add 20 mmol of thiophene-3-acetic acid, 25 mmol of hexafluoroisopropanol, 1.5 g of 4-dimethylaminopyridine, 1.7 g of N,N'-carbonyldiimidazole and 50 mL of chloroform into a three-necked flask equipped with a stirrer and a thermometer, stir and react for 20 min at a temperature of 30 °C and a stirring rate of 300 r / min, then continue to stir and react for 12 h under the condition of heating to 85 °C. After the reaction is completed, cool the reaction product to room temperature, then rotary evaporate to remove the solvent, then add it to distilled water, then extract 3 times with dichloromethane, combine the extraction liquid and dry it with anhydrous magnesium sulfate, then vacuum filter, rotary evaporate the filtrate to remove the solvent, and then carry out column chromatography purification with a mixed eluent composed of ethyl acetate and n-hexane in a volume ratio of 1:10 to obtain the modified thiophene monomer;

[0067] Step 3: Add 1 g of carboxylated carbon nanotubes and 60 mL of chloroform into a three-necked flask equipped with a stirrer and a thermometer, ultrasonically disperse for 3 h under the condition of an ultrasonic frequency of 40 kHz, then add 30 mmol of modified thiophene monomer and stir and react for 3 h under the conditions of a temperature of 30 °C and a stirring rate of 300 r / min. Then add 80 mmol of anhydrous ferric chloride and continue to stir and react for 30 h. After the reaction is completed, vacuum filter the reaction product, wash the filter cake with absolute ethanol and distilled water 5 times in sequence, and then place it in a vacuum drying oven and dry for 10 h under the condition of a temperature of 55 °C to obtain the wave-absorbing stealth composite material for unmanned aerial vehicles.

[0068] The wave-absorbing stealth composite materials for unmanned aerial vehicles in Examples 2-4 and Comparative Examples 1-4 were uniformly mixed with melted solid paraffin at a mass ratio of 1:4, made into coaxial rings with an outer diameter of 7.0 mm, an inner diameter of 3.0 mm, and a thickness of 3.0 mm. Then, an N5234A vector network analyzer was used to test the electromagnetic parameters of the coaxial ring samples in the frequency range of 2-18 GHz, and further calculate the maximum reflection loss value RL and the effective absorption bandwidth GHz to evaluate the wave-absorbing performance of the materials.

[0069] The test results are shown in the following table:

[0070]

[0071] Referring to the data in the above table, according to the comparison between Examples 2-4 and Comparative Examples 1-4, it can be known that the wave-absorbing stealth composite material for unmanned aerial vehicles of the present application has the ability of wide frequency band and high-efficiency absorption, and exhibits excellent electromagnetic wave absorption performance.

[0072] In the description of this specification, the descriptions referring to terms such as "one embodiment", "example", "specific example", etc. mean that the specific features, structures, materials or characteristics described in connection with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in a suitable manner in any one or more embodiments or examples.

[0073] The above content is only an example and illustration of the present invention. Those skilled in the art of this technology can make various modifications or supplements to the described specific embodiments or use similar methods for substitution, as long as they do not deviate from the invention or exceed the scope defined by this application, they should all fall within the protection scope of the present invention.

Claims

1. An absorbing and stealth composite material for an unmanned aerial vehicle, characterized in that It is composed of a modified polythiophene coated on the outside of a supported carbon nanotube. Among them, the supported carbon nanotube is formed by carboxylated carbon nanotubes supporting iron tetroxide. Among them, the modified polythiophene is polymerized from modified thiophene monomers; Among them, the supported carbon nanotube is prepared by the following steps: Stir and react carboxylated carbon nanotubes, ferric chloride hexahydrate, ferrous sulfate heptahydrate, and deionized water. Then, while stirring, gradually dropwise add an ammonia water solution. After the addition is complete, continue stirring and reacting. Then, add anhydrous ethanol and continue stirring and reacting. After the reaction ends, cool the reaction product, and then perform solid-liquid separation. Wash and dry the solid to obtain the supported carbon nanotube.

2. The radar-absorbing stealth composite material for an unmanned aerial vehicle according to claim 1, characterized in that The dosage ratio of the carboxylated carbon nanotubes, ferric chloride hexahydrate, ferrous sulfate heptahydrate, deionized water, ammonia water solution, and anhydrous ethanol is 2g: 3mmol: 6mmol: 40 - 50mL: 20 - 25mL: 10 - 15mL; the mass fraction of the ammonia water solution is 26 - 28%.

3. The radar-absorbing stealth composite material for an unmanned aerial vehicle according to claim 1, characterized in that, The carboxylated carbon nanotube is prepared by the following steps: Stir and react carbon nanotubes, concentrated sulfuric acid, and concentrated nitric acid. After the reaction ends, cool the reaction product, and then centrifuge. Wash and dry the precipitate to obtain the carboxylated carbon nanotube.

4. The radar-absorbing stealth composite material for an unmanned aerial vehicle according to claim 3, wherein, The dosage ratio of the carbon nanotubes, concentrated sulfuric acid, and concentrated nitric acid is 2g: 10 - 15mL: 30 - 35mL.

5. The radar-absorbing stealth composite material for unmanned aerial vehicle according to claim 3, characterized in that, The diameter of the carbon nanotubes is 30 - 40nm, and the length is 5 - 10μm; the mass fraction of the concentrated sulfuric acid is 96 - 98%; the mass fraction of the concentrated nitric acid is 66 - 68%.

6. The radar-absorbing stealth composite material for an unmanned aerial vehicle according to claim 1, wherein The modified thiophene monomer is prepared by the following steps: Stir and react thiophene-3-acetic acid, hexafluoroisopropanol, 4-dimethylaminopyridine, N,N'-carbonyldiimidazole, and chloroform. After the reaction ends, cool the reaction product, then perform rotary evaporation. Then, add it to distilled water, and then extract. Dry the extract with anhydrous magnesium sulfate, then perform vacuum filtration. Rotary evaporate the filtrate, and then perform column chromatography purification with a mixed eluent to obtain the modified thiophene monomer.

7. The radar-absorbing stealth composite material for an unmanned aerial vehicle according to claim 6, wherein, The dosage ratio of the thiophene-3-acetic acid, hexafluoroisopropanol, 4-dimethylaminopyridine, N,N'-carbonyldiimidazole, and chloroform is 20mmol: 23 - 25mmol: 1.1 - 1.5g: 1.3 - 1.7g: 40 - 50mL.

8. An electromagnetic wave absorbing stealth composite material for an unmanned aerial vehicle according to claim 6, characterized in that, The mixed eluent is a mixture of ethyl acetate and n-hexane in a volume ratio of 1: 8 - 10.

9. A preparation method of a radar-absorbing stealth composite material for an unmanned aerial vehicle, characterized in that, It includes the following steps: Ultrasonically disperse the supported carbon nanotubes and chloroform, then add the modified thiophene monomer and stir and react. Then, add anhydrous ferric chloride and continue stirring and reacting. After the reaction ends, perform vacuum filtration on the reaction product. Wash and dry the filter cake to obtain the microwave absorption stealth composite material for drones.

10. The preparation method of a radar-absorbing stealth composite material for an unmanned aerial vehicle according to claim 9, characterized in that, The dosage ratio of the supported carbon nanotubes, chloroform, modified thiophene monomer, and anhydrous ferric chloride is 1g: 50 - 60mL: 10 - 30mmol: 40 - 80mmol.